Analisis Kualitas Pelayanan Administrasi Kependudukan dalam Meningkatkan Kepuasan Masyarakat di Kecamatan Balongbendo - Varrell Fernanda Maesa Ayu; Erlina Yunanti (RIGGS: Journal of Artificial Intelligence and Digital Business, 2026)
The fulfillment of public needs for civil registration documents is highly dependent on the quality of services provided by government institutions. Based on this issue, this study aims to analyze the quality of population administration services in supporting public satisfaction in Balongbendo Subdistrict, Sidoarjo Regency. This research employed a qualitative approach with a descriptive method. Data were collected through observation, in-depth interviews, and documentation. The research informants consisted of the Head of the Service Section, employees responsible for population administration services, and community members who had used the services. The data analysis process was carried out through several stages, including data collection, data reduction, data presentation, and conclusion drawing, using the Miles and Huberman model. The findings indicate that the services have generally been implemented well. This is reflected in the friendly attitude of the employees, their willingness to assist the public, and the delivery of information that is easy to understand. However, several obstacles remain in the service process, particularly queues at certain times and incomplete administrative requirements submitted by some community members. Therefore, improvements in service efficiency and facility comfort are needed to provide the public with a better service experience.